A case of infective endocarditis mimicking antineutrophil cytoplasmic antibody-associated vasculitis. Issue 1 (July 2022) - Doi, Kosuke; Minami, Kimihito; Ishigami, Kenjiro; Ikeda, Syuhei; Hamatani, Yasuhiro; Yoshizawa, Takashi; Ide, Yuya; Fujino, Akiko; Ishii, Mitsuru; Iguchi, Moritake; Ogawa, Hisashi; Masunaga, Nobutoyo; et al.
Abstract: Infective endocarditis (IE) is not a common disease, but it remains a serious condition. Antineutrophil cytoplasmic antibodies (ANCA) are often positive in IE, and discrimination between IE and ANCA-associated vasculitis is important because misdirected selection of therapy can lead to catastrophic consequences. We report a case of IE mimicking ANCA-associated vasculitis in which we were able to make a correct diagnosis and perform treatment. This case suggests that it is important to consider IE as a differential diagnosis in ANCA-positive patients. Learning objective: Antineutrophil cytoplasmic antibodies (ANCA) are associated with primary systemic vasculitis. However, ANCA have also been described in other conditions and infective endocarditis (IE) was considered an important cause of ANCA. Discrimination between IE and ANCA-associated vasculitis is important, although it is sometimes difficult. We report a case of IE mimicking ANCA-associated vasculitis. ANCA-positive patients with nonspecific symptoms should be suspected of having IE, checked for heart murmurs, and tested by echocardiography and blood cultures.